2022
DOI: 10.3390/atmos13050714
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Burden of Heatwaves in Sydney, Australia Is Exacerbated by the Urban Heat Island and Climate Change: Can Tree Cover Help Mitigate the Health Impacts?

Abstract: Heatwaves are associated with increased mortality and are exacerbated by the urban heat island (UHI) effect. Thus, to inform climate change mitigation and adaptation, we quantified the mortality burden of historical heatwave days in Sydney, Australia, assessed the contribution of the UHI effect and used climate change projection data to estimate future health impacts. We also assessed the potential for tree cover to mitigate against the UHI effect. Mortality (2006–2018) records were linked with census populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…High environmental temperatures are a known risk factor for dogs developing HRI. 46 The current results show that the highest rates of HRI occurred in 2004 and 2016, which corresponds to heatwave years 32 and see Figure 5 that shows the number of days with temperatures above the 95th percentile. Similarly, most HRI cases presented in months with elevated air temperatures, with most being reported in December/January which aligns with the Australian summer.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…High environmental temperatures are a known risk factor for dogs developing HRI. 46 The current results show that the highest rates of HRI occurred in 2004 and 2016, which corresponds to heatwave years 32 and see Figure 5 that shows the number of days with temperatures above the 95th percentile. Similarly, most HRI cases presented in months with elevated air temperatures, with most being reported in December/January which aligns with the Australian summer.…”
Section: Discussionmentioning
confidence: 69%
“…The monthly HRI incidence rates peaked in December and January during the Australian summer ( Figure 4). The highest incidence rate of HRI was reported in 2004 and 2016 (Figure 6), which corresponds with hotter years in Sydney 32 and see Figure 5).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…2 Extreme heat as a public health climate change impact Human metabolic temperature sits roughly around 35°C. Humans function most efficiently in environments below this temperature (Nairn and Fawcett, 2013) and problems arise for the human body when average temperatures rise over 35°C or remain above 30°C across a 24 h period (Chaston et al, 2022). Heatwaves are generally defined as abnormally hot weather that lasts for a period of 48 h or more (Nairn and Fawcett, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…They create an isolated heat island with its detached microclimate apart from nearby rural areas [2,3]. Some studies reported that mortality rates increased significantly in urban areas due to summer heat waves entangled with UHI [1,[4][5][6]. The fast-growing urban sprawl or urban expansion contributes to this increasing heat.…”
Section: Introductionmentioning
confidence: 99%